Edukasi Kesehatan Terhadap Pengetahuan Terkait Perilaku Bullying pada Anak Usia Sekolah Dasar - Niriyah, Sekani; Utami, Agnita; Roslita, Riau (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2024)
The development of social interaction and self-confidence in children can experience obstacles due to bullying incidents that occur to children at school. Bullying in schools is still a problem in Indonesian education, because many school-age children do not understand much about bullying behavior that they do or get from the environment. Efforts to increase the prevention of bullying behavior can be carried out by increasing knowledge of the impact of bullying through the implementation of education. The purpose of this study is to see the effectiveness of health education on knowledge related to bullying behavior in elementary school children. This research is a quantitative study with a pre experimental design without control group with a one group pretest- posttest design with a total research sample of 30 students. The results showed that there was a significant difference in knowledge between sntsrs drbrlum before health counseling and after health counseling with p = 0.001. Education about bullying behavior is effective in an effort to increase knowledge and the dangers of bullying behavior so that it can prevent bullying behavior in schools.